STUDY THE RELATIONSHIP BETWEEN CULTURAL COMPETENCE AND LEARNING MANAGEMENT IN THE 21st CENTURY IN PRIVATE ISLAMIC SCHOOLS IN THE SPECIAL DEVELOPMENT OF THE SOUTHERN BORDER PROVINCES - Boonrat, Arisra; Tritrisual, Triphumin; Boonprakarn, Kettawa; Sangkaphan, Jedsarid; Kaewmano, Chaowanee; Kotcharat, Jutarat; Pannitayaphong, Warachai; Sa-U, Samsoo (Journal of MCU Nakhondhat, 2025)
This research examined the relationship between cultural competence and 21st century learning management in private Islamic schools in the special development of the southern border provinces. The research was quantitative research. The samples were 400 teachers in private Islamic schools in the Southern Border Special Development Area. The cluster sampling method was used. The research instruments were the Cultural Competence Questionnaire and the 21st Century Learning Management Questionnaire in a 5-level rating scale with a reliability of 0.914 and .894. The statistics used to analyze the data were percentages and Pearson's product moment correlation coefficient. The results of the research found that teachers in private Islamic schools In the southern border provinces, 307 females, or 76.75 percent, 93 males, or 23.75 percent, 223 aged 30 and under, or 55.75 percent, 177 aged 31 and over, or 44.25 percent, 158 working years or over, or 39.50 percent, 127 working years or under, or 31.75 percent, and found that all 5 cultural competencies had a positive relationship with learning management in the 21st century, both overall and in all 8 aspects, with statistical significance at the .01 level. Considering each aspect, it was found that cultural competencies in terms of global perspective had the highest positive relationship with learning management in the 21st century, followed by understanding others and adaptability. The aspect with the lowest relationship was cultural sensitivity.